The Role of Principal Transformational Leadership on Effectiveness School Organizational Culture - Abubakar, Faisal; Laoh , Rahman; Ode Riniati , Wa; Mokodompit , Haslinda; Putra , Purniadi (Mudir : Jurnal Manajemen Pendidikan, 2023)
The objective of this study is to depict the transformative leadership of school principals in constructing the organizational culture within educational institutions. The approach employed is qualitative, utilizing data collection methods such as interviews, documentation, and observation. The procedure for analyzing the data consists of data collection, data reduction, data presentation, and conclusion. To ensure the validity of the data, tests were conducted to establish credibility, transferability, dependability, and confirmability. The discoveries indicate that the principal's transformative leadership is effective in establishing a strong organizational culture. Principals develop specific programs that foster a culture within schools. In determining which programs to implement, principals involve all stakeholders within the educational institution. To cultivate the organizational culture, principals serve as exemplary role models for all members of the school, thereby facilitating the successful implementation of a positive organizational culture. As leaders, principals consistently provide motivation to the entire teaching staff, both through verbal and written means, in both general and specific contexts. Principals promote self-awareness among teachers and foster effective communication, ensuring that social interactions run smoothly.